Europe’s COVID-19 Crisis Response: A Race Well Run, But Not Yet Won - Alfred Kammer; Nathaniel Arnold (Intereconomics)
Abstract While Europe’s response to the pandemic has been laudable, there remains more to be done in order to prevent economic scarring and ensure a robust recovery.